Complications of epi- and endocardial pacing in children. (14th October 2021) - Dzhaffarova, O; Svintsova, L; Plotnikova, I
Abstract: Aim: To analyze complications of cardiac pacing in children depending on the implantation method. Actuality: Recently epicardial lead implantation becomes more and more popular either due to more serious complications of transvenous pacing or due to possibility of choice of hemodynamically optimal pacing zone. Methods and materials: 242 patients with pacemakers are under our supervision. Epicardial pacemakers were implanted to 145 patients, endocardial – to 97 patients. In "old era" in most children the primary epicardial implantations were performed at RV free wall. In 27 children, having primary implantation at our Institute lately, the epicardial lead was placed at LV apex, or endocardial – at RV apex. Results: The comparative analysis of complications of epi- and endocardial implantation showed the following results: 22% of complications at epicardial stimulation, and at transvenous stimulation – 45%. The most often complications at epicardial stimulation (53%) were connected with hemodynamic disorders – dyssinchronous cardiomyopathy. Hemodynamic complications, connected with dyssinchrony of endocardial RV pacing, were disclosed in 16%. The most often complication of endocardial stimulation was TV insufficiency (32%). Venous vessel thrombosis was diagnosed in 9%. Epicardial and transvenous lead failure was discovered in similar percentage ratio (28%). Infectious complications of transvenous pacing, especially, bacterial endocarditis, took place in 6, 8%. Thus, progressive bacterial endocarditis and TV insufficiency (3d deg.) appeared in one patient in 10 years after the primary implantation. Afterwards, elimination of endocardial system by open surgery, TV plasty followed by epicardial pacing implantation are required. Infection of pacing site was disclosed in both types of implantation (1%). Perforation of atrial endocardial lead was found in two cases (4%). A case of mechanical complication (cardiac strangulation) was diagnosed in a child (3%) in four years after the primary implantation of epicardial pacing system. Pericarditis was recorded immediately after the epicardil pacemaker implantation in 9% of cases. Our center performs epicardial lead implantation with the help of midline sternotomy that provides clear approach to right atrium. However, the difficulties of lead fixation at LV apex appear here. It concerns, especially, the patients after CHD correction as the repeated sternotomy in them presents high risk of RV insufficiency. Nevertheless, the given approach is still the best possible with epicardial pacing if there is a "preclude", sufficient experience of CHD correction. Conclusion: The possibility of choice of optimal epicardial pacing site exceeds risks of leads and midline sternotomy. Any primary pacemaker implantation in children of any age with ventricular lead should be epicardial. Funding Acknowledgement: Type of funding sources: None.